Large-scale Multi-item Auctions : Evidence from Multimedia-supported Experiments - Schweitzer, Sascha Michael (KIT Scientific Publishing, 2012)
This book presents two experimental studies that deal with the comparison of multi-item auction designs for two specific applications: the sale of 2.6 GHz radio spectrum rights in Europe, and the sale of emissions permits in Australia. In order to tackle the complexity of these experiments, a cognitively based toolkit is proposed, including modularized video instructions, comprehension tests, a learning platform, a graphical one-screen user interface, and comprehension-based group matching.